USAHA PERIKANAN TERPADU DI FAKULTAS PERIKANAN UNIVERSITAS PGRI PALEMBANG - Helmi Haris; Tri Widayatsih; Asmawati Asmawati (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
The Faculty of Fisheries, University of PGRI Palembang has two campuses, namely at Campus A Plaju for administrative and lecture activities, while for practical activities, field practice, research and training, specifically for the Faculty of Fisheries located at Campus C Sematang Borang-Palembang. Campus C Sematang This place occupies about 1 ha of land, which has been equipped with Office Room facilities, Multipurpose Room for meetings, Lecture Rooms, Fish Hatchery Workshop, Fisheries Product Processing Workshop, Entrepreneurship Workshop, Fish Feed Production Room, Cement Pond for seeding, Bioflog for enlargement and floating net cages for enlargement. Campus C is specifically intended for the Fisheries Faculty which was completed in 2012. In 2013 and 2014 the Chair of the Proposal Team received Community Service Grant as Team Leader for the Campus Innovation Product Business Development Program Scheme (PPUPIK) entitled